Emerging trends in IoT for aquatic systems: a systematic literature review - Cohen-Manrique, Carlos; Camacho-Leon, Sergio; Villa, Jose Luis (Frontiers in Water, 2025)
Climate change, pollution, and the overexploitation of water resources have intensified global water scarcity, particularly in arid and semi-arid regions. This systematic literature review analyzes 458 peer-reviewed articles published between 2015 and 2025 to identify the main IoT-based technological strategies applied to the monitoring and management of surface and groundwater systems. Following PRISMA guidelines, the studies were categorized into four thematic areas: IoT applications in aquatic environments, data transmission technologies, algorithms for process optimization and data analysis, and sensor fusion techniques. The results show that LoRa is the most widely adopted transmission technology due to its long-range coverage, scalability, and low energy consumption. Emerging innovations such as remote IoT, satellite-assisted sensing, and digital twins are also gaining relevance as transformative tools for real-time hydrological monitoring. Overall, the findings reveal a shift toward more integrated and intelligent IoT frameworks and include a recommended architecture for aquatic systems. Despite these advancements, the review highlights the need for more accessible, affordable, and interoperable IoT solutions to enable broader adoption, particularly in resource-constrained regions, and to support sustainable water resource management.